2021
DOI: 10.12962/j23546026.y2020i1.10854
|View full text |Cite
|
Sign up to set email alerts
|

Building Information Modeling (BIM) Technology Acceptance Analysis Using Technology Acceptance Model (TAM)

Abstract: The growth of an industry growth couldn't be separated from technology development. Nowadays, technology development mostly affected by digitalization, which brought us to industry 4.0 era. The same thing also occurs in construction industry, although its development relatively slower than the growth in manufacturing industry. Construction technology, such as Building Information Modeling (BIM), 3D printing, and robotic equipments, has been introduced to construction industry. BIM is defined as digital represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…According to (Son et al, 2014, p. 3), perceived ease of use is "the degree to which a user believes that a technology will be easy to understand and will require no effort to use." Several studies have shown that perceived ease of use can significantly impact individuals' attitudes toward the implementation of BIM (Davis, 1989;Prihatono & Adi, 2021;Scherer, Siddiq, & Tondeur, 2019;Yuan, Yang, & Xue, 2019). One of the interesting findings from the articles by (Thong, Hong, & Tam, 2002) and (Wang & Song, 2017) is the indirect influence of PEOU on user acceptance of digital libraries.…”
Section: Hypothesis 1 Computer Self-efficacy Will Influence (H1a) Kno...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to (Son et al, 2014, p. 3), perceived ease of use is "the degree to which a user believes that a technology will be easy to understand and will require no effort to use." Several studies have shown that perceived ease of use can significantly impact individuals' attitudes toward the implementation of BIM (Davis, 1989;Prihatono & Adi, 2021;Scherer, Siddiq, & Tondeur, 2019;Yuan, Yang, & Xue, 2019). One of the interesting findings from the articles by (Thong, Hong, & Tam, 2002) and (Wang & Song, 2017) is the indirect influence of PEOU on user acceptance of digital libraries.…”
Section: Hypothesis 1 Computer Self-efficacy Will Influence (H1a) Kno...mentioning
confidence: 99%
“…Following Wang and Song (2017), it can be inferred that individuals would deem a system as valuable or useful if it is easy to use. Hence, importance was placed on the PEOU to be considered for BIM implementation in organisations within the construction industry (Prihatono & Adi, 2021;Wang & Song, 2017). PEOU of BIM can be improved if organisations are more flexible in accepting new technologies (Lee & Yu, 2016).…”
Section: Hypothesis 1 Computer Self-efficacy Will Influence (H1a) Kno...mentioning
confidence: 99%
“…The Cronbach's alpha coefficient, which assesses the internal consistency and has a minimum acceptable value of 0.70, is used to determine the reliability of scales [38]. The SEM methodology was taken into account, because it provides a useful way to assess different study hypotheses [38][39][40][41][42][43][44][45]. SEM is an effective statistical technique that is utilized in studies to examine and comprehend intricate relationships between latent (unobservable) factors and apparent variables [38].…”
Section: Data Analysis Techniquesmentioning
confidence: 99%
“…If students have high intensity in using gadgets, students will often use the internet for studying purpose and by doing so students will get good learning outcomes. In addition, Priatno and Marantika [24] stated that utilizing information technology has a positive influence on children's achievement, if they remain under parental supervision.…”
Section: Influence On Academic Achievementmentioning
confidence: 99%